PENGARUH PERUBAHAN TARIF, METODE PENGHITUNGAN DAN MODERNISASI SISTEM PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DENGAN KEADILAN PAJAK SEBAGAI VARIABEL MODERASI - Thahir, Ade Nuryunita; Karyadi, Iman; Azmi, Yanis Ulul (Jurnal Analisa Akuntansi dan Perpajakan, 2021)
This research was conducted to determine and test the effect of changes in tax rates (X1), tax calculation methods (X2) and modernization of the tax system (X3) on MSME taxpayer compliance with tax justice as a moderating variable (M). As for the population in this study, the UMKM taxpayers in the food and beverage sector are registered at the Surabaya City Trade Office. Data collection uses purposive sampling method, provided that the taxpayer has a NPWP and has a gross turnover (turnover) in one tax year not to exceed Rp4.8 billion. The samples used in this study were 80 respondents. Data analysis in this study used multiple linear regression and interaction regression with the help of SPPS version 17. The results of the study using multiple linear regression analysis showed that partially changes in tax rates did not have a positive effect and insignificant on taxpayer compliance, while the tax calculation method and tax system modernization partially have a positive and significant effect on taxpayer compliance. Multiple regression analysis with the interaction test for variable changes in tax rates to taxpayer compliance with tax justice as a moderating variable, the method of calculating taxes against taxpayer compliance with tax justice as a moderating variable and modernization of the tax system towards taxpayer compliance with tax fairness as a moderating variable partial positive and significant effect which means that tax justice is able to moderate all the variables used in this study.